2020
DOI: 10.3329/birdem.v10i2.47734
|View full text |Cite
|
Sign up to set email alerts
|

Relation between plasma lipids and relapse of idiopathic nephrotic syndrome in children

Abstract: Background: Nephrotic syndrome (NS) is one of the most common renal diseases in children. It is a chronicchildhood disorder with a course of relapse and remission. Hyperlipidemia is a constant feature (95% cases)of minimal change nephrotic syndrome (MCNS) having serum cholesterol >250 mg/dl. Both increased synthesisand decreased clearance of lipoproteins may contribute to the hyperlipoproteinemia which frequently complicatesthe NS. Persistent hyperlipidemia can lead to relapse of NS which is a potential ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…As other variables remained constant, children with high serum triglyceride levels at remission had a 2.74 times greater hazard of relapse than those with a serum triglyceride level below 110 mg/dl. It was in agreement with the studies done in Bangladesh (44%) (35), India (56%) (36), and Ethiopia (88%), (14), which showed that elevated triglyceride levels during remission were a predictor of relapse. Congruently, in this study, 52% of children with elevated triglyceride levels experienced relapse.…”
Section: Discussionsupporting
confidence: 92%
“…As other variables remained constant, children with high serum triglyceride levels at remission had a 2.74 times greater hazard of relapse than those with a serum triglyceride level below 110 mg/dl. It was in agreement with the studies done in Bangladesh (44%) (35), India (56%) (36), and Ethiopia (88%), (14), which showed that elevated triglyceride levels during remission were a predictor of relapse. Congruently, in this study, 52% of children with elevated triglyceride levels experienced relapse.…”
Section: Discussionsupporting
confidence: 92%
“…Other studies also reported persistent lipid abnormalities during a prolonged period of disease remission ( 5 - 7 ). According to the results from previous studies, hyperlipidaemia during remission predicts relapse in idiopathic NS ( 21 , 22 ). The survival rate of children with NS has remarkably improved with corticosteroid therapy.…”
Section: Discussionmentioning
confidence: 89%
“…Mahmud et al, 2011 concluded that increased serum cholesterol levels during the remission phase might be associated with subsequent relapse in NS, and total serum cholesterol may be regarded as a predictor of relapse in childhood Idiopathic NS 28 . Kabir et al, 2020 reported that only the triglyceride level during remission was a risk factor in relapsing NS 23 .…”
Section: Discussionmentioning
confidence: 99%